EXPLORING JUNIOR HIGH SCHOOL STUDENTS’ CRITICAL THINKING PROCESSES IN SOLVING SYSTEMS OF LINEAR EQUATIONS USING GEOGEBRA: A QUALITATIVE CASE STUDY - kuirinus iventri; Agung Lukito; Pradnyo Wijayanti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Critical thinking is an essential cognitive skill in mathematics learning, particularly in solving contextual and non-routine problems. However, many junior high school students still experience difficulties in applying critical thinking when solving systems of linear equations. This study aims to explore the critical thinking processes of students in solving systems of linear equations in two variables (SPLDV) using GeoGebra. A qualitative descriptive approach with a case study design was employed. The participants were 25 ninth-grade students from a junior high school in Surabaya, Indonesia. Based on the results of a critical thinking test, three students were purposively selected to represent successful, less successful, and unsuccessful problem solvers. Data were collected through GeoGebra-assisted problem-solving tasks and semi-structured interviews, and analyzed using Facione’s critical thinking framework: interpretation, analysis, inference, evaluation, explanation, and self-regulation. The findings reveal that successful students demonstrated all six critical thinking processes consistently, while less successful students showed partial fulfillment of the indicators. Unsuccessful students failed to demonstrate most critical thinking processes due to weak conceptual understanding and poor problem interpretation. GeoGebra supported visualization and verification of solutions but did not replace conceptual reasoning. These findings highlight the importance of integrating technology with explicit instruction on critical thinking processes in mathematics learning.